Tindak Tutur Ekspresif dalam Gelar Wicara Mata Najwa dan Implikasinya dalam Kegiatan Literasi pada Pembelajaran Bahasa Indonesia - Destriawan, Bayu (Jurnal Didaktika Pendidikan Dasar, 2023)
This research was conducted to examine the form of speech and selection strategies as well as in literacy activities in schools. The aims of this study are (a) to describe the form of expressive speech acts, (b) to describe the strategies for speaking in expressive speech acts, (3) and to imply literacy activities in learning. This type of research is a qualitative research with descriptive method. The data of this research are expressive utterances of speech and speech partners in the speech title of Mata Najwa. Data was collected through the look method. The data analysis technique is carried out, (1) searching, (2) classifying, (3) interpreting, (4) making conclusions about the data that has been analyzed. The results of this study consist of two findings. First, in the speech title Mata Najwa found eight expressive acts, namely (a) thanking, (b) congratulating, (c) sorry, (d) praising, (e) praising, (f) complaining, (g) blame, and (h) insinuate. Second, in the speech title of Mata Najwa in expressive speech acts, four strategies were found, namely (a) the strategy of speaking frankly without further ado, (b) the strategy of speaking frankly with positive politeness, (c) the strategy of speaking in a simple language. -Basic politeness is negative, and (d) speaking vaguely. Based on the results of the study, it can be said that the speech in the Mata Najwa speech title can be used as a literacy activity in learning Indonesian.